Scheduling of multi-fuel energy resources in microgrid using grey wolf optimisation. (7th December 2022) - Dubey, Salil Madhav; Dubey, Hari Mohan; Pandit, Manjaree
Implementation of a microgrid (MG) to establish an independent, efficient, and cost-effective power supply system is the need of the hour. The generation in MG can be conventional or non-conventional. Still, due to increasing power demand, high fuel prices, scarcity of fossil fuels, and degrading the environment, there is a growing demand for renewable energy sources (RS) for power generation. Multi-fuel power sources like solar, wind, fuel cells, etc., improve the adequacy, and increase supply reliability, provide a dynamic response. This paper discusses the dynamic scheduling of MGs in two different systems with distinguishing distributed generation (DG) units. Grey wolf optimisation (GWO), a meta-heuristic technique inspired by the hierarchical hunting mechanism of grey wolves, is used in this paper to solve a multi-objective problem in a dynamic environment. The performance and effectiveness of GWO are compared and validated with methods like CSA, ABC, DE, and PSO.